2020
DOI: 10.1093/mnras/staa153
|View full text |Cite
|
Sign up to set email alerts
|

Direct collapse to supermassive black hole seeds: the critical conditions for suppression of H2 cooling

Abstract: Observations of high-redshift quasars imply the presence of supermassive black holes (SMBHs) already at z ∼ 7.5. An appealing and promising pathway to their formation is the direct collapse scenario of a primordial gas in atomic-cooling haloes at z ∼ 10 − 20, when the H 2 formation is inhibited by a strong background radiation field, whose intensity exceeds a critical value, J crit . To estimate J crit , idealized spectra have been assumed, with a fixed ratio of H 2 photo-dissociation rate k H 2 to the H − pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 108 publications
1
24
0
Order By: Relevance
“…The effects of alternative choices are small in thin media, but become important in dense sites (e.g. when estimating molecular cooling of collapsing gas or critical fluxes of impinging radiation during the formation of massive black-hole seeds; Luo et al 2020;Maio et al 2019). Neglecting HI shielding corrections at high redshift (z > 5) leads to a large degree of H ionisation and H 2 photodissociation, causing underestimation of HI and H 2 cosmological densities and leading to a trend of the atomic and molecular density parameters in tension with data even at z < 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of alternative choices are small in thin media, but become important in dense sites (e.g. when estimating molecular cooling of collapsing gas or critical fluxes of impinging radiation during the formation of massive black-hole seeds; Luo et al 2020;Maio et al 2019). Neglecting HI shielding corrections at high redshift (z > 5) leads to a large degree of H ionisation and H 2 photodissociation, causing underestimation of HI and H 2 cosmological densities and leading to a trend of the atomic and molecular density parameters in tension with data even at z < 5.…”
Section: Discussionmentioning
confidence: 99%
“…36 of Draine & Bertoldi (1996) unless otherwise stated. In the case of Wolcott-Green et al (2017), the optimal scale at which to estimate the local H 2 column density, N H 2 , and related shielding have been investigated in depth by Luo et al (2020). These latter authors showed that N H 2 can be quantified as N H 2 = n H 2 λ J /4, where n H 2 is the the three-dimensional H 2 number density and λ J the Jeans length.…”
Section: Gas Hi and H 2 Self Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, unlike Johnson et al (2013), we use the same value to both Pop III and II stars, and it is fLW = 15. The LW radiation can be attenuated locally due to self-shielding gas (e.g., Draine & Bertoldi 1996;Glover & Brand 2001;Wolcott-Green et al 2011Luo et al 2020). To take the self-shielding effect into account, we evaluate the column density over the local Jeans length as follows:…”
Section: Hiimentioning
confidence: 99%
“…Gas self-shielding (e.g. Draine & Bertoldi 1996;Rahmati et al 2013;Hartwig et al 2015;Wolcott-Green et al 2017;Ploeckinger & Schaye 2020;Luo et al 2020;Walter et al 2020), limits the ability of UV radiation to penetrate dense material and preserves HI or H 2 fractions in star forming regions. The relevance and the relative role of the two main (HI and H 2 ) shielding processes for chemical abundances in cosmic environments need to be further explored, though.…”
Section: Introductionmentioning
confidence: 99%